2013
DOI: 10.5935/1678-9741.20130077
|View full text |Cite
|
Sign up to set email alerts
|

Results of medium-term survival in patients undergoing cardiac transplantation: institutional experience

Abstract: Introduction The heart transplant became a consecrated therapy for patients with terminal heart failure, increasingly improving the survival. Objective To identify the medium-term results in patients undergoing cardiac transplantation. Methods This is a descriptive, documentary and retrospective study, using a quantitative approach, developed in a Unit of Transplant and Heart Failure, of a tertiary level public hospital, located in Fortaleza, CE, Brazil. The data were obtained from a sample of 188 patients (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…It was observed, in relation to the conditioning factors for self-care, that the highest percentage of heart transplant patients were male, which result was similar in other studies [9,10]. In relation to the age, there was a prevalence of the range of 50 to 59 years (38.1%).…”
Section: Discussionsupporting
confidence: 77%
“…It was observed, in relation to the conditioning factors for self-care, that the highest percentage of heart transplant patients were male, which result was similar in other studies [9,10]. In relation to the age, there was a prevalence of the range of 50 to 59 years (38.1%).…”
Section: Discussionsupporting
confidence: 77%
“…For example, in our population, the mean age at transplant was 53.5 (±11.8) years, whereas in Leiden [ 5 ], the mean age was 49 (±14) years; the difference may not be significant but shows a trend toward younger recipients. Furthermore, in the Brazilian population, the cause of transplantation was related to Chagas disease in 17.2% of patients [ 6 ], in contrast to our population, which had no cases of Chagas disease. Differences are also related to donors, organ procurement, immunosuppression, and periprocedural strategies [ 7 ].…”
Section: Discussionmentioning
confidence: 58%
“…Two previous studies also observed a protective association between increasing recipient age and mortality. 10,11 One possible explanation for the protective association may be due to the confounding effect of congenital heart disease, as these patients are significantly younger compared with all other heart failure etiologies, and have the highest risk of 1-year mortality. 1 In addition, older heart transplant candidates are less likely to have comorbidities due to the careful candidate selection process, which could minimize their post-operative risk.…”
Section: Relation To Earlier Studiesmentioning
confidence: 99%